2017 23rd International Conference on Automation and Computing (ICAC) 2017
DOI: 10.23919/iconac.2017.8081995
|View full text |Cite
|
Sign up to set email alerts
|

Planetary gearbox fault diagnosis using an on-rotor MEMS accelerometer

Abstract: Abstract-Conventional accelerometers installed on housing often give out less accurate diagnostic results for planetary gearbox because the mesh excitation of planet gears change with carrier movement. Recent significant advancements in low-power and low-cost Micro-Electro-Mechanical Systems (MEMS) technologies make it possible and easier to mount MEMS accelerometers directly on the rotating shaft, enabling more accurate dynamic characteristics of the rotating machine to be acquired and used for condition moni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Although MEMS accelerometer are convenient to be embedded into the interior of the rotating machinery, the impact of gravity's force brought by the accelerometer themselves should not be ignored, Mones [12] et al installed two MEMS accelerometers radially relative to each other on the input shaft of the planetary gearbox, using the sensor gravity acceleration in the tangential direction of the shaft of the projected direction of the opposite direction of the offset, to reduce the impact of gravity acceleration on the collected signals, and experiments have shown that this approach can be a more accurate characterization of the dynamics of the rotor. Although this method can eliminate the effect of gravity acceleration of the sensors, it requires the installation of two MEMS accelerometers in the relative radial direction, which is not only costly, but also affects the results due to the error caused by the installation position.…”
Section: Introductionmentioning
confidence: 99%
“…Although MEMS accelerometer are convenient to be embedded into the interior of the rotating machinery, the impact of gravity's force brought by the accelerometer themselves should not be ignored, Mones [12] et al installed two MEMS accelerometers radially relative to each other on the input shaft of the planetary gearbox, using the sensor gravity acceleration in the tangential direction of the shaft of the projected direction of the opposite direction of the offset, to reduce the impact of gravity acceleration on the collected signals, and experiments have shown that this approach can be a more accurate characterization of the dynamics of the rotor. Although this method can eliminate the effect of gravity acceleration of the sensors, it requires the installation of two MEMS accelerometers in the relative radial direction, which is not only costly, but also affects the results due to the error caused by the installation position.…”
Section: Introductionmentioning
confidence: 99%
“…Employing MEMS sensors in PHM is not new (Lee, 2011;Bechhoefer, Wadham-Gagnon, & Boucher, 2012), but only relatively recently low-cost high-frequency MEMS sensors became commercially available. The potential of lower-cost MEMS sensors have been grabbing the attention of PHM researchers: instrumenting planetary gearbox with MEMS accelerometers (Mones et al, 2017); showing the promised of use piezoelectric MEMS accelerometers for PHM in industrial applications (Xuewen Gong, Wu, Liao, & Gong, 2020); and investigating fault detection using capacitive MEMS accelerometer array (Watson & Reichard, 2021). The feasibility of using microphones for Engine diagnostics has been discussed by (Mathew & Zhang, 2020).…”
Section: Introductionmentioning
confidence: 99%